Taheebo Polyphenols Attenuate Free Fatty Acid-Induced Inflammation in Murine and Human Macrophage Cell Lines As Inhibitor of Cyclooxygenase-2 - Ma, Sihui; Yada, Koichi; Lee, Hyunjin; Fukuda, Youichi; Iida, Akira; Suzuki, Katsuhiko (Frontiers in Nutrition, 2017)
Aim of study Taheebo polyphenols (TP) are water extracts of Tabebuia spp. (Bignoniaceae), taken from the inner bark of the Tabebuia avellanedae tree, used extensively as folk medicine in Central and South America. Some anti-inflammatory drugs act by inhibiting both cyclooxygenase-2 (COX-2) and COX-1 enzymes. COX-2 syntheses prostaglandin (PG) E2, which is a species of endogenous pain-producing substance, whereas COX-1 acts as a house-keeping enzyme. Inhibiting both COX-1 and 2 simultaneously can have side-effects such as gastrointestinal bleeding and renal dysfunction. Some polyphenols have been reported for its selective inhibiting activity towards COX-2 expression. Our study aimed to demonstrate the potential and mechanisms of TP as an anti-inflammation action without the side-effects of COX-1 inhibition. Materials and methods Free fatty acid (FFA)-stimulated macrophage cell lines were employed to mimic macrophage behaviors during lifestyle-related diseases such as atherosclerosis and non-alcoholic steatohepatitis. RT-PCR was used to detect expression of inflammatory cytokine mRNA. Griess assay was used to measure the production of nitric oxide (NO). ELISA was used to measure prostaglandin (PG) E2 production. Molecular docking was adopted to analyze the interactions between compounds from Tabebuia avellanedae and COX-2. Results TP significantly suppressed the production of NO production, blocked the mRNA expression of iNOS, and COX-2 in both cell lines, blocked the mRNA expression of TNF-α, IL-1β, IL-6 and PGE2 in the murine cell line. However, there was no inhibitory effect on COX-1. Molecular docking result indicated that the inhibitory effects of TP on COX-2 and PGE2 could be attributed to acteoside, which is the main compound of TP that could bind to the catalytic zone of COX-2. After the interaction, catalytic ability of COX-2 is possibly inhibited, followed by which PGE2 production is attenuated. COX inhibitor screening assay showed TP as a selective inhibitor of COX-2 enzyme. Conclusions The anti-inflammatory effects of TP can possibly regulate macrophages due to the targeted inhibition of COX-2 activity, without affecting COX-1 activity with other anti-inflammatory effects including suppression of iNOS and inflammatory cytokines. As such, TP is potentially useful in prevention and treatment of lifestyle-related disease by attenuating inflammation caused by macrophages infiltration.